2000
DOI: 10.2307/3284961
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Trichinellosis in Reindeer

Abstract: Six female reindeer calves were inoculated intraruminally with various doses of Trichinella muscle larvae. Four calves were inoculated with T. nativa, receiving 15,000 (n = 1), 5,000 (1), and 2,500 (2) larvae each. Two calves were inoculated with 5,000 T. spiralis larvae each. Blood samples were collected twice per week for total white blood cell (WBC) and differential counts and for serology using enzyme-linked immunosorbent assay (ELISA) based on T. spiralis excretory-secretory antigen. On day 56, the calves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2002
2002
2006
2006

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…in sheep, but in that study, they used Trichinella pseudospiralis with a very high dose of larvae per animal. Oksanen et al (2000) reported a serological response from the 23rd day p.i. in reindeers experimentally infected with T. spiralis and Trichinella nativa.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…in sheep, but in that study, they used Trichinella pseudospiralis with a very high dose of larvae per animal. Oksanen et al (2000) reported a serological response from the 23rd day p.i. in reindeers experimentally infected with T. spiralis and Trichinella nativa.…”
Section: Discussionmentioning
confidence: 97%
“…In Europe, no outbreak of human trichinellosis has been attributed to the consumption of ruminant meat, but in Asia, sheep, cow, and wild moufflon (Ovis musimon) are occasional sources of infection (Zhu and Niu 1988;Liu and Boireau 2002). There have been reports on the following studies in experimentally infected, nonspecific ruminant hosts: (Smith and Snowdon 1988;Smith et al 1989;Tomašovičová et al 1991;Pajerský et al 1996;Reina et al 1996;Oksanen et al 2000;Theodoropoulos et al 2000).…”
Section: Introductionmentioning
confidence: 89%
“…It is a well-known fact that Trichinella larvae are not evenly distributed throughout the skeletal musculature [1,9,21,20,14]. Obviously, hind leg muscles are the predilection of trichinellosis in rats, and the lower lpg yield in minced meat indicates the dilution effect of other musculature and tissue.…”
Section: Discussionmentioning
confidence: 99%